On the variability of the surface environment response to synoptic forcing over complex terrain: A multivariate data analysis approach - Halios, C.H.a; Helmis, C.G.a; Flocas, H.A.a; Nyeki, S.b; Assimakopoulos, D.N.a (Meteorology and Atmospheric Physics, 2012)
Synoptic climatology relates the atmospheric circulation with the surface environment. The aim of this study is to examine the variability of the surface meteorological patterns, which are developing under different synoptic scale categories over a suburban area with complex topography. Multivariate Data Analysis techniques were performed to a data set with surface meteorological elements. Three principal components related to the thermodynamic status of the surface environment and the two components of the wind speed were found. The variability of the surface flows was related with atmospheric circulation categories by applying Correspondence Analysis. Similar surface thermodynamic fields develop under cyclonic categories, which are contrasted with the anti-cyclonic category. A strong, steady wind flow characterized by high shear values develops under the cyclonic Closed Low and the anticyclonic H-L categories, in contrast to the variable weak flow under the anticyclonic Open Anticyclone category. © 2012 Springer-Verlag.
cited By (since 1996)0
Keywords: anticyclone; atmospheric circulation; Climatology; Multivariate Analysis; principal component analysis; steady flow; suburban area; Synoptic meteorology; terrain; thermodynamics; topography